The Effect of Profitability, Leverage, and Firm Size on ERC in the Industrials Sector on the IDX. - Mohamad Zulman Hakim; Humaidi Abbas; Imas Kismanah; Mulyadi Mulyadi; Hustna Dara Sarra; Kimsen Kimsen (Cita konsultindo, 2023)
Abstract. Effect of Profitability, Leverage, and Company Size on Earnings Response Coefficient. The purpose of this study is to empirically examine the effect of profitability, leverage, and firm size on the earnings response coefficient by using accounting conservatism. This study uses secondary data on Industrial companies listed on the IDX and which generate profits in 2019-2021. The sampling technique used purposive sampling method and obtained as many as 22 companies with an observation period of 3 years. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that profitability has no effect on the earnings response coefficient and firm size does not have a significant effect on the earnings response coefficient, but leverage has a positive effect on the earnings response coefficient.